Café Atmosphere, Food Quality, and Variety: Impact on Revisit Intention via Customer Satisfaction - Rahmadi, Nizar; S, Syahbandi; H, Heriyadi; Pebrianti, Wenny (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aimed to test the influence of Cafe Atmosphere, Food Quality, and Product Variety on Revisit Intention with Customer Satisfaction as a mediating variable at Lokale Coffee West Borneo. The study used a quantitative approach with survey method and data processing using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Data were obtained from 175 respondents who had visited Lokale Coffee at least twice. The results of the study showed that Cafe Atmosphere, Food Quality, and Product Variety positively and significantly affected Customer Satisfaction, which subsequently significantly affected Revisit Intention. Additionally, Cafe Atmosphere and Product Variety also have a direct influence on Revisit Intention, while Food Quality only provides an indirect influence through Customer Satisfaction. Of the ten hypotheses tested, nine were declared accepted. The findings show that Cafe Atmospher comfortable, quality food, and menu diversity offered are key factors in increasing customer satisfaction and loyalty. This research provides a practical contribution for cafe management in designing a satisfactory experience-based customer retention strategy.